3-D model of a radial flow sub-watt methanol fuel processor. (2nd October 2015) - Holladay, J.D.; Wang, Y.
Abstract: A 3-D model is presented for a novel sub-watt packed bed reactor. The reactor uses an annular inlet flow combined with a radial flow packed bed reactor. The baseline reactor is compared to a reactor with multiple outlets and a reactor with 3 internal fins. Increasing the outlets from 1 to 4 may have improved flow distribution, but did not increase the performance. However, inserting fins allowed >99% methanol conversion with approximately 30 K decrease in temperature with same inlet flow. Highlights: Micro-scale methanol fuel processor with a radial flow design is modeled. Two types of performance improvements over the baseline reactor are proposed and modeled. By including fins in the reactor design, the numerical simulation predicts a 2.7× increase in performance.